JURNAL INGGRIS ANGKLUNG TRAINING FOR PAUD TEACHERS - sulastri sulastri (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2019)
West Java is the area that is rich in traditional music, one of them is angklung, which is a musical instrument made of bamboo and played by shaking . As one of the traditional musical instruments, angklung as musical instrument should be maintained by the community so that it can still be heard and played and even preserved to the next generation. One effort to appreciate and preserve angklung traditional music, IGTKI (Bandung Kindergarten Teachers Association) held a Training to improve the professional competence of early childhood education teachers as a target audience in mastering traditional angklung music to be able to transfer knowledge to children early age in PAUD. The purpose of this study  analyzed the implementation of angklung extracurricular learning in PAUD in Bandung as a vehicle for the preservation of traditional music in West Java. This study uses qualitative descriptive as the method. Data collection techniques used were observation, interviews, and documentation. By preserving angklung traditional music, it is hoped that angklung music will remain a cultural heritage of West Java without fear of being seized by other countries.Keywords; Training, Education Teachers, PAUD, Angklung